Common Weed Hosts of Insect-Transmitted Viruses of Florida Vegetable Crops - Gaurav Goyal; Harsimran K. Gill; Robert McSorley (EDIS)
This 12-page fact sheet expands upon and updates the information on several weeds reported as virus hosts by UF/IFAS plant pathologists in 2001 and provides links to further information on specific viruses that affect vegetable crops. Written by Gaurav Goyal, Harsimran K. Gill, and Robert McSorley, and published by the UF Department of Entomology and Nematology, April 2012.